The development email notification via shoutbox / Mohd Khairul Mat Daud - Mat Daud, Mohd Khairul (2007)
In UiTM, information delivery is one of the most important elements to make lecturers and students become a better information society. Information must be quickly delivered and received by lecturers and students in a timely manner. Nowadays, in the Faculty of Information of Technology and Quantitative Sciences (FTMSK), an ineffective communication approach is still being used to deliver information to students and lecturers such as using notice board, sms and phone call. Therefore, email notification via shoutbox has developed and can be considered as a potential approach to achieve this objective. Shoutbox is use to display the information that we need to inform quickly but in this project the shoutbox can be able to send the information to certain people via their email simultaneously. Email notification via shoutbox allow user especially lecturer and students to communicate, make announcement and give information easily, provident and reduce their time. The function of this project is to make user sending the information very convenient and in a timely way.